The Influence of the Electronic Document Management System (EDMS) on Organizational Performance Through Operational Efficiency, Decision Making and Document Security at the Regional Office of the Ministry of Religion, West Sulawesi Province - Hajrah, Sitti; Muhammad Ridwan Arif, Hasniaty Hasniaty , (Pascasarjana STIE Amkop Makassar, 2023)
This research aims to analyze the extent to which the implementation of the use of EDMS in managing organizational documents as a digital transformation in the archives sector is able to improve organizational performance through operational efficiency, decision making and document security at the Regional Office of the Ministry of Religion, West Sulawesi Province.The research approach used in this research is qualitative and quantitative methods with explanatory and descriptive approaches. From the total population data, the Slovin formula was used to obtain a sample of 125 respondents.These results show that the path coefficient between variables is that EDMS Implementation has a positive and significant effect on Operational Efficiency, EDMS Implementation directly affects Decision Making, EDMS Implementation has a positive and significant effect on Document Security, EDMS Implementation has no direct effect on Organizational Performance. EDMS has an indirect effect on organizational performance through Operational Efficiency, EDMS Implementation indirectly has an effect on Organizational Performance through Decision Making and EDMS Implementation indirectly has a positive and significant effect on Organizational Performance through Document Security, Operational Efficiency has a positive effect on organizational performance, decision making decisions have a positive effect on organizational performance, document security has a positive effect on organizational performance at the Regional Office of the Ministry of Religion, West Sulawesi Province. Keywords: EDMS, Decision Making, Document Security, Efficiency and Organizational Performance